(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
ABSTRACT:This article examines the profound influence of folk culture on American literature, emphasizing its role in shaping narrative forms, themes, and cultural identity. Folk traditions—encompassing oral storytelling, myths, legends, music, and rituals—have served as a vital foundation for many American literary works. By analyzing contributions from diverse communities, including Native American, African American, and immigrant groups, the study highlights how folk culture enriches literature with authenticity and a sense of collective memory. Key examples from authors such as Mark Twain, Zora Neale Hurston, and William Faulkner demonstrate how folklore informs storytelling techniques and deepens cultural expression. The article concludes by exploring how folk culture continues to inspire contemporary writers, ensuring its enduring legacy in American literary traditions.